AN ANTHROPOLOGICAL LINGUISTIC STUDY: LANGUAGE AND GENDER IN EFL CLASSROOM - Maharani, Anak Agung Putri (Jurnal Santiaji Pendidikan (JSP), 2020)
Gender differences are pivotal in EFL (English as A Foreign Language) classroom. The aims of this anthropological linguistic study are to figure out the extent of female and male learners’ differences in EFL classroom, the factors which affect the gender differences in the EFL learners’ language use, and the effects that learners’ gender differences in language use bring to the EFL classroom. Having been designed as a conceptual study, several research findings were scrutinized to answer the research questions. It can be wrapped up that both male and female are distinctive in using English as an international language due to the reasons in communication. Further, it was revealed that multiple factors affect gender differences in using language within the EFL classes; such as: classroom environment, cultural, and social impacts. Finally, the findings definitely convey positive impacts towards the future EFL teaching and learning process.